Optimization and fabrication of electrospun PCL poly (ε-caprolactone) fiber diameter and 3D scaffold for tissue engineering - Lim, Marcus Zhi Wei. (2009)
Electrospinning of scaffolds using a (biocompatible) polymer solution for tissue engineering is an approach that is gaining popularity. In order to increase the potential that a scaffold can bring in the biomedical field, reduction of fiber diameters and optimization of scaffold porosity through the fabrication of a three-dimensional (3D) scaffold to improve on the capabilities of existing two-dimensional (2D) scaffolds that has to be carried out. In this study, Poly ( -caprolactone) was the material used for the electrospun scaffold. The study was divided into three parts. Firstly, manipulation of various polymer solution and electrospinning machine chamber parameters to optimize fiber diameters was performed. Once optimum fiber diameters was obtained, a novel method of electrospinning on a conductive, needle-like target was done to produce spherical 3D scaffolds. At the same time, electrospinning of fibers was also conducted on PCL Rapid Prototype Scaffolds (RPS) acting as a framework for production of 3D scaffolds. The optimum solution mixture obtained consisted of Dichloromethane (DCM) for dissolving PCL and N,N-Dimethylforamide (DMF) as an additive to increase solution conductivity in the ratio of 3.5:6.5. Machine parameters were set at a voltage of 18kV and a feed rate of 0.5ml/h. The 3D scaffolds electrospun using both methods using these parameters were subjected to morphological characterization. The 3D scaffolds showed obvious signs of porosity and tests show that the level of penetration was more than 90%. Unfortunately, the spinning of 3D scaffolds with a PCL RPS did not yield a 3D nonwoven PCL structure. While the project was able to lead to optimization of fiber parameters and show that scaffolds have a relatively high level of porosity, the utilization of the RPS can be developed further. Despite these limitations, the potential benefits a 3D electrospun scaffold can bring makes it a promising area worthy of further improvement. Future studies could be engineered towards the direction of improvement of the RPS electrospinning techniques to build 3D scaffolds in alternate ways.